The prevalence of pterygium recurrences and associated risk factors at the Universitas Academic Hospital Complex in Bloemfontein - Engelbrecht, C. (University of the Free State, 2019)
Aim: To find the prevalence of and associated risk factors of pterygium recurrences in patients who underwent pterygium surgery at the Universitas Academic Hospital Complex. Methods: A retrospective cross sectional study of all the patients who underwent pterygium surgery at the Universitas Academic Hospital Complex between January 2016 and December 2018. All patients who received their primary surgery at the Universitas Academic Hospital Complex were included. Results: A total of 117 eyes from 94 patients who underwent pterygium surgery were identified. The proportion of females was 80% (n=94). Ages ranged from 20 to 75 years with a median age of 49 years. Most patients (83%) presented 6 months after noticing symptoms related to the pterygium. These symptoms included: redness (30%), tearing (13%) and foreign body sensation (10%). Inflammation was noted in 21% of patients. The most common surgical procedure performed on these patients was a conjunctival autograft (74%), followed by a conjunctival rotational flap (10%), amnion graft (10%) and bare sclera (2,5%). The bare sclera technique was used in a total of 3 cases, 2 of these cases (66,7%) had a recurrence. A conjunctival autograft was used in 86 cases, of these 10 cases (11,6%) had a recurrence. In a total of 17 cases where a conjunctival rotation flap was used, 3 patients (17%) had a recurrence. An amnion graft was used in 12 patients, 6 of them (50%) had a recurrence. The total recurrence rate was 21 (18%). Conclusion: Postoperative recurrences are a common complication of pterygium surgery. Compared to the bare sclera technique and amnion grafts, conjunctival autografts and conjunctival rotational flaps had lower recurrence rates.
Keywords: Dissertation (M.Med. (Ophthalmology))--University of the Free State, 2019; Pterygium surgery; Bare sclera technique; Conjunctival autograft; Amnion graft; Conjunctival rotation flap